2012
DOI: 10.1248/bpb.b110714
|View full text |Cite
|
Sign up to set email alerts
|

Effects of 3-<i>O</i>-Methyldopa, <small>L</small>-3,4-Dihydroxyphenylalanine Metabolite, on Locomotor Activity and Dopamine Turnover in Rats

Abstract: It has been well known that 3-O-methyldopa (3-OMD) is a metabolite of L-3,4-dihydroxyphenylalanine (L-DOPA) formed by catechol O-methyltransferase (COMT), and 3-OMD blood level often reaches higher than physiological level in Parkinson's disease (PD) patients receiving long term L-DOPA therapy. However, the physiological role of 3-OMD has not been well understood. Therefore, in order to clarify the effects of 3-OMD on physiological function, we examined the behavioral alteration in rats based on locomotor acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 22 publications
(24 reference statements)
1
10
0
Order By: Relevance
“…The current results indicated that striatal AADC levels in the treatment groups increased within 48 h compared with the control group, which was consistent with the observation that striatal DA levels within 48 h were elevated compared with levels in the hippocampus and cortex. Furthermore, DA may be degraded into DOPAC by MAO-B and into HVA by COMT (5,6). In the present study, striatal levels of MAO-B and COMT in the treatment groups were reduced compared with the control group, which may explain why the (DOPAC + HVA)/DA ratio in the striatum was reduced compared with the control group during 48 h.…”
Section: Discussionsupporting
confidence: 45%
See 1 more Smart Citation
“…The current results indicated that striatal AADC levels in the treatment groups increased within 48 h compared with the control group, which was consistent with the observation that striatal DA levels within 48 h were elevated compared with levels in the hippocampus and cortex. Furthermore, DA may be degraded into DOPAC by MAO-B and into HVA by COMT (5,6). In the present study, striatal levels of MAO-B and COMT in the treatment groups were reduced compared with the control group, which may explain why the (DOPAC + HVA)/DA ratio in the striatum was reduced compared with the control group during 48 h.…”
Section: Discussionsupporting
confidence: 45%
“…L-dopa is subsequently converted into DA by aromatic amino acid decarboxylase (AADC) (4). In addition, DA is converted into 3,4-dihydroxyphenylacetic acid (DOPAC) by monoamine oxidase B (MAO-B) (5), and into homovanillic acid (HVA) by catechol-O-methyltransferase (COMT) (6). Therefore, L-dopa, DA, DOPAC, HVA, AADC, MAO-B, COMT and TH may be implicated in the pathogenesis of PD.…”
Section: Introductionmentioning
confidence: 99%
“…The intracerebroventricular injection of 3-OMD reduced DA turnover and locomotor activity while it impaired DA uptake in rat striatal membranes and PC12 cells and increased oxidative stress [112]. The behavioral and neurochemical effects of 3-OMD are still present upon sub-chronic intracerebroventricular administration [112,113]. Upon local application on mixed cultured mesencephalic neurons and striatal astrocytes, L-DOPA displayed neuroprotective effects on DA neurons via the involvement of astrocytes.…”
Section: Metabolites Of L-dopamentioning
confidence: 99%
“…The choice of the doses was based on the results of previous studies [8,42,43]. Ranitidine and cS-induced catalepsy to NCT.…”
Section: Drugs and Dosesmentioning
confidence: 99%